Efisiensi Sel Surya Polimer Tandem Dengan Penambahan Bahan Aktif PPV: PCBM dan P3HT: PCBM - Restu, Angga Fauzan (RC-INSTITUT, 2019)
Tandem polymer solar cells are one of the potential candidates as an alternative energy source that produces electricity. Light absorption is carried out by active coating with material P3HT:PCBM and PPV: PCBM which is semiconductor. This study aims to determine the effect of the Cooper (II) Oxide (CuO) concentration and increase the amount of material coating on the active layer with variations in coating on topcell and bottomcell on the performance of solar cells. The XRD characterization results showed an influence on the crystal structure of the adsorption coefficient of CuO because the better the structural K of CuO , where the CuO Crystal structure was determined by the value of Crystal or ACS ( Average Cristal Size), the best value of ACO CuO at concentration 0 , 75M CuO with a value of 23,525 nm . The results of SEM characterization showed that CuO had a more uniform and homogeneous layer morphology. The highest efficiency is obtained from the comparison of P3HT: PCBM on topcell and PPV: PCBM on bottomcell (2: 1) which is 4.37 % with current strength of 0.0 5 mA and voltage of 4.098 V.   Keywords: Tandem Polymer Solar Cells P3HT,PCBM,PPV, CuO Semiconductors, Efficiency, SEM , XRD.